Police training in responding to family, domestic and sexual violence - Dowling, Christopher (Trends & issues in crime and criminal justice, 2024)
Police in Australia are seeing increased reporting of family, domestic and sexual violence, while facing greater pressure to secure positive outcomes for victims. Improvements in the training police receive in responding to this violence have been identified as critical to broader efforts to reduce it. This study reviews published Australian and international research on police training in responding to family, domestic and sexual violence. The last few decades have seen a significantly expanded focus on family, domestic and sexual violence as part of police training. This, along with several notable training innovations, have underpinned a shift in police training needs from more basic concerns around correct procedure and knowledge of the law, to more advanced concerns including recognising and investigating coercive control and identifying primary aggressors. Overall, police are receptive and responsive to training, but certain types of training, particularly those with strong practical and problem-solving components, hold more promise.